KORELASI MOTIVASI DENGAN HASIL BELAJAR MATA PELAJARAN SOIOLOGI KELAS X IPS SMAN 8 PONTIANAK - Tiara Jelita Sianturi; Yohanes Bahari; Riama Alhidayah (Universitas Tanjungpura, 2019)
AbstractThis study aims to know the close relationship between learning motivation with learning outcomes of 1th grade of social class students in sociology in senior high school 8. The research method used was descriptive quantitative research. The data source of this study was the 1th grade of social class students in sociology in senior high school 8 and the data is the result of the mid-semester assessment of the grade of social class students in sociology in senior high school 8. The results showed that students' learning motivation in class 1th sociology subjects in Social Sciences at State senior high school 8 Pontianak was very high, with an average achievement of 82.98. Based on the results of the percentage of intrinsic motivation of students in class 1th grade of social class students in sociology in senior high school 8, with a percentage level of 93.12% and extrinsic motivation is high, with a percentage of 80.49%. There is a significant relationship between motivation and student learning outcomes in class 1th grade of social class students in sociology in senior high school 8 with a strong relationship with a correlation of 0.736. While the contribution of the influence of motivation with student learning outcomes by 54.2% and the remaining 45.8% is influenced by other factors.Keywords: Relationship, Motivation, Learning outcomes.